Why Explicit Knowledge Cannot Become Implicit Knowledge. (4th November 2016) - VanPatten, Bill
Abstract: In this essay, I review one of the conclusions in Lindseth (2016) published in Foreign Language Annals . That conclusion suggests that explicit learning and practice (what she called form‐focused instruction) somehow help the development of implicit knowledge (or might even become implicit knowledge). I argue for a different interpretation of the results based on the nature of language as mental representation and the nature of acquisition. I argue that explicit knowledge cannot become implicit knowledge or help its development as characterized by Lindseth. Instead, the results can be interpreted as learners simply getting faster with explicit knowledge.